Regulation of the Launch of Orphan Drugs on the Market of the Eurasian Economic Union as a Mechanism to Increase the Availability of Treatment for Rare Diseases (Review) - A. V. Foteeva; N. A. Koneva; O. S. Beloglazova; N. B. Rostova (Разработка и регистрация лекарственных средств)
Introduction. Providing high-quality, effective and safe drugs intended for the treatment of rare (orphan) diseases among the population of the Member States of the Union is one of the most significant and promising development vectors for manufacturers-developers. Ensuring the availability of medicines (MP) for patients suffering from rare diseases should be regulated by state incentives for the development and launch of orphan drugs on the market by domestic manufacturers through updating and timely updating of regulatory legal acts in the field of drug registration, as well as providing benefits when initiating the registration process.Text. The article assessed the possibilities and prospects for the introduction of orphan drugs into circulation within the framework of the Eurasian Economic Union for domestic manufacturers.Conclusion. A review of the possibilities and prospects for launching orphan drugs for domestic manufacturers indicates the need to develop regulatory and legal regulation of aspects of pharmaceutical development in order to increase the availability of treatment for patients with rare diseases, both at the level of the Russian Federation and within the legal framework of the Eurasian Economic Space.